Activity, Selectivity, and Durability of Ruthenium Nanoparticle Catalysts for Ammonia Synthesis by Reactive Molecular Dynamics Simulation: The Size Effect - Kim, Sung-Yup; Lee, Hong Woo; Pai, Sung Jin; Han, Sang Soo (American Chemical Society, 2018)
We report a molecular dynamics (MD) simulation employing the reactive force field (ReaxFF), developed from various first-principles calculations in this study, on ammonia (NH3) synthesis from nitrogen (N-2) and hydrogen (H-2) gases over Ru nanoparticle (NP) catalysts. Using ReaxFF-MD simulations, we predict not only the activities and selectivities but also the durabilities of the nanocatalysts and discuss the size effect and process conditions (temperature and pressure). Among the NPs (diameter = 3, 4, 5, and 10 nm) considered in this study, the 4 nm NPs show the highest activity, in contrast to our intuition that the smallest NP should provide the highest activity, as it has the highest surface area. In addition, the best selectivity is observed with the 10 nm NPs. The activity and selectivity are mainly determined by the hcp, fcc, and top sites on the Ru NP surface, which depend on the NP size. Moreover, the selectivity can be improved more significantly by increasing the H2 pressure than by increasing the N2 pressure. The durability of the NPs can be determined by the mean stress and the stress concentration, and these two factors have a trade-off relationship with the NP size. In other words, as the NP size increases, its mean stress decreases, whereas the stress concentration simultaneously increases. Because of these two effects, the best durability is found with the 5 nm NPs, which is also in contrast to our intuition that larger NPs should show better durability. We expect that ReaxFF-MD simulations, along with first-principles calculations, could be a useful tool in developing novel catalysts and understanding catalytic reactions.
Keywords: FORCE-FIELD; 1ST-PRINCIPLES CALCULATIONS; STRUCTURE SENSITIVITY; OXIDE CATALYSTS; REAXFF; ADSORPTION; OXIDATION; NITROGEN; RU(0001); SURFACES